2015
DOI: 10.1021/acs.inorgchem.5b00687
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydrogen Elimination Mechanism in the Absence of Low-Lying Acceptor Orbitals in EH2(t-C4H9) (E = N–Bi)

Abstract: The β-hydrogen elimination reactions of group 15 alkyl compounds at the example of EH2(t-C4H9) (element E = N-Bi) were investigated and compared to the group 13 example of GaH2(t-C4H9). With the aid of extensive density functional theory based analysis of atomic and electronic structures at the transition state, we can derive three distinct reaction classes. The gallium compound follows the well-known β-hydride route with participation of an empty p orbital at the metal in a concerted, synchronous fashion, exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…reported that there are two decomposition pathways, first a free radical process producing isobutane and second a β-H-elimination process, that generates isobutene as a side product 30 , 31 . Hence, the observations made in these experiments as well confirm β-H-elimination as the main decomposition mechanism at temperatures above 390 °C 32 , 33 .…”
Section: Resultssupporting
confidence: 81%
“…reported that there are two decomposition pathways, first a free radical process producing isobutane and second a β-H-elimination process, that generates isobutene as a side product 30 , 31 . Hence, the observations made in these experiments as well confirm β-H-elimination as the main decomposition mechanism at temperatures above 390 °C 32 , 33 .…”
Section: Resultssupporting
confidence: 81%
“…[31,32] It thus allows to characterize the nature of transition states and provides a microscopic picture on the crucial changes in the molecule along the minimum energy path with the largest influence on the reaction barrier. [33] The first finding is an asymmetric profile of the transition region (grey area). The TS is positioned rather close to the product and the minimum of the force constant curve (green) does not coincide with the maximum of the energy (black circles).…”
Section: Methodsmentioning
confidence: 98%
“…Those characteristics are indicative of a non-concerted reaction where bond-breaking and bond-making do not happen simultaneously along the reaction path as has been found before for the -H elimination of group 15 alkyls. [33] An analysis of the bond lengths along the reaction path ( Fig. 2) confirms that the S-F bond is only slightly elongated at the beginning of the transition region (deviation from value in 2, ∆d(SF) = +0.227 Å) while the S-N bond is already close to its value at the TS (deviation from value at TS: ∆d(SN) = +0.190 Å, see also the animated IRC in the supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…8(a)) and without ( Fig. 37,38 From Table 1, it is found that b-hydride eliminations exhibit moderately high electronic barriers, which increase only slightly with increasing temperature. This simulates the growth in H 2 and Ar atmospheres since in the latter case, reactions with H 2 is not possible.…”
Section: Gas Phase Cvd Chemistry Of Tebmentioning
confidence: 97%